Optimization of Natural Food Preservatives Extraction from Spices and Herbs - Ibtesam, I. Ahmed; Mohamed, B. Atta; Habib, E. Mostafa (Food Technology Research Journal)
Bio preservatives is a natural compound deprived from plants used as a natural food preservation to preserve food and extend their shelf life. The extraction optimization and chemical composition of clove, cinnamon, thyme and fennel were investigated as a natural preservative materials. The extraction optimization conditions were investigated by using different ratio of sample to solvent as follow (1:5, 1:10, 1:15 and 1:20 w/v) at different stirring period (1, 2, 3 and 4 hours) and at different concentrations of ethanol in water (80, 60, 40, 20 and 0%) were determined. Moreover, Phytochemicals constitutes of different studied plants including; total soluble polyphenols; flavonoids, alkaloids and saponin were determined in their alcoholic extracts (80%). The data shown that: ethanol in general, gave the highest total soluble solid (TSS) recovery than water. Moreover, 80% ethanol was the most effective in TSS recovery during the extraction process than the other concentrations for clove, cinnamon and thyme. The TSS value of clove, cinnamon and thyme (recovered by 80% ethanol) were 18.2%, 16.72% and 16.33 % plant, respectively. However, fennel water extract conducted 9.17% when compared with 80% ethanol extract which amounted 9%. The chemical composition of secondary metabolites phytochemicals namely phenolic compounds, saponine, flavonoids and alkaloids which expected to have antibacterial activity, were determined in clove, cinnamon and thyme plants. Data show that no significant difference in phenolic contents between clove and cinnamon. While thyme contained the lowest amounts of phenolic compounds. On the other hand, thyme contained the significant highest amounts (2.63 mg/g dry weight) of alkaloids among the other studied plants.